Sistem Informasi Pendaftaran DNA Sexing Report Awan Bird Berbasis Java - Arif Setiawan; Yuni Wibawanti; Aulia Ar Rahman Awaludin (Universitas Indraprasta PGRI Jakarta, 2020)
Information technology that is engaged in the DNA Sexing Report test business or registration of the DNA Sexing Report is a system that is still rarely used by businesses engaged in the field of DNA sexing. Awan Bird Business is a business with a registration system and the calculation is still fairly manual where the system has not been computerized. The purpose of this study is to make a design of an application for the DNA Sexing Report Registration Information System that can carry out the registration system activities and DNA test payments and report making more efficiently. The method the author uses to create a DNA Sexing Report registration information system using the programming language Java Netbeans and MySQL. The author uses Java Netbeans IDE 8.0.2 for making programs and MySQL as a database storage facility. The results of the system that was built can facilitate the admin in the process of registering DNA Sexing Report and payment of DNA Sexing Report so that it is easier to find data.